Why Americans don't join the party : race, immigration, and the failure (of political parties) to engage the electorate - Hajnal, Zoltan, 1968-; Lee, Taeku (Book collections on Project MUSE., 2011)
Two trends are dramatically altering the American political landscape: growing immigration and the rising prominence of independent and nonpartisan voters. Examining partisan attachments across the four primary racial groups in the United States, this book offers the first sustained and systematic account of how race and immigration today influence the relationship that Americans have--or fail to have--with the Democratic and Republican parties. Zoltan Hajnal and Taeku Lee contend that partisanship is shaped by three factors--identity, ideology, and information--and they show that African Ame.